DIALOGUE AND LEARNING ON SOCIAL VULNERABILITY AND SPIRITUALITY (CIPEEX, 2025)
Dialogue about the realities experienced by people in situations of vulnerability is essential to broaden social understanding, develop empathy, and promote inclusion, constituting a fundamental practice in the training of socially conscious and responsible professionals. In this context, this text describes an experience carried out through a conversation circle held in the second semester of 2024, within the discipline of Citizenship, Ethics and Spirituality, with the participation of students and professors from the Administration program at the Evangelical University of Goiás – Rubiataba Campus, as well as members of the Fazenda Esperança community, a therapeutic institution that works in the recovery of drug dependents based on the tripod of work, coexistence, and spirituality. The action aimed to promote reflection and dialogue on the challenges faced by people in situations of vulnerability, addressing themes such as self-care, social reintegration, chemical dependency, and the positive impact of spirituality and ethics in the recovery process. The methodology combined collaborative planning, definition of objectives, logistical organization, preparation of a detailed schedule, mobilization of participants, bibliographic review on the subject, and contact with the guests, including the director and a sponsor of Fazenda Esperança, who shared their personal and professional experiences. During the conversation, students observed in practice the application of theoretical concepts of management, effective communication, commitment, professional ethics, and teamwork in complex social contexts. Among the main challenges faced in carrying out this action were the reconciliation of schedules and the provision of financial resources, which were overcome with institutional support. The results showed high engagement and satisfaction of the participants, as well as the strengthening of interpersonal competencies, leadership skills, planning, and organization of academic activities with social purpose. The experience also allowed students to deepen their understanding of diversity, inclusion, social sensitivity, and ethics, reinforcing the relevance of collaborative work and social engagement in academic training. It is concluded that the proposed action represented an enriching opportunity for learning, personal growth, and professional development, preparing students to act more consciously, empathetically, and competently in contexts of social vulnerability.
Keywords: Vulnerability; Spirituality; Administration; Learning